A new species of Pentacalia (Senecioneae: Asteraceae) from Northern Peru - Sagástegui, Abundio (2009)
Pentacalia vallejiana Sagást. & E. Rodr. sp. nov. is described as a new species of Pentacalia Cassini - (Senecioneae: Asteraceae) from the Department of La Libertad, Peru. This new species is apparently endemic to the province of Santiago de Chuco. Pentacalia vallejiana is a remarkable Peruvian species and peculiar within the genus. It is compared with its closest relative and data on its geographical distribution and ecology are provided.